Age Differences in Consumer Decision Making under Option Framing: From the Motivation Perspective - Peng, Huamao; Xia, Shiyong; Ruan, Fanglin; Pu, Bingyan (Frontiers in Psychology, 2016)
Option framing effect is the phenomena that participants often accept more options when they are asked to delete undesired options from a full model (subtractive framing) than they do when they are instructed to add desired options to a base model (additive framing). Whether the same effect exists in different age groups is less well known. To explore the roles of age and purchase motivations on the option framing effect for automobiles purchases, this study adopted a 3(age group: younger, middle-aged, vs. older) ×2(option framing: additive vs. subtractive) ×2(focus condition: information vs. emotion) mixed design. To manipulate purchase motivations, participants in the three age groups were instructed to focus on the ratio of utility and price of options (information-focus) or the extent of pleasure induced by the options (emotion-focus) when they made purchase decisions in two framing conditions. The results revealed similar option framing effect across all age groups in the information-focus condition regarding the total price paid for accepted options. In contrast, the framing effect was not found in the emotion-focus condition. In addition, older adults accepted more options and an overall higher price than younger and middle-aged adults in both focus conditions. This difference was more obvious in the emotion-focus condition than in the information-focus condition. Moreover, both the number of accepted options and the total accepted price of the younger group in the information-focus condition were higher than those in the emotion-focus condition, whereas the older and middle-aged groups accepted same number of options and price between two focus conditions. These results imply that purchase motivation is a moderator of the option framing effect and age characteristics linked with motivations must be considered in sales.